2017
DOI: 10.1093/mnras/stx783
|View full text |Cite
|
Sign up to set email alerts
|

NGC 6067: a young and massive open cluster with high metallicity

Abstract: NGC 6067 is a young open cluster hosting the largest population of evolved stars among known Milky Way clusters in the 50 -150 Ma age range. It thus represents the best laboratory in our Galaxy to constrain the evolutionary tracks of 5 -7 M stars.We have used high-resolution spectra of a large sample of bright cluster members (45), combined with archival photometry, to obtain accurate parameters for the cluster as well as stellar atmospheric parameters. We derive a distance of 1.78 ± 0.12 kpc, an age of 90 ± 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 115 publications
(186 reference statements)
8
34
0
Order By: Relevance
“…This result might seem at odds with previous findings of a solar or sub-solar metallicity for young and intermediate-age clusters (see, e.g., D'Orazi et al 2011;Spina et al 2017, and references therein). However, it is in agreement with what is expected from standard chemical evolution (e.g., Minchev et al 2013, and references therein) and recent results of a super-solar metallicity ([Fe/H] ≈ +0.2) for some young or intermediate-age clusters in the solar neighborhood, such as NGC 6067 (Alonso-Santiago et al 2017) and Praesepe (D'Orazi et al 2019).…”
Section: Discussionsupporting
confidence: 91%
“…This result might seem at odds with previous findings of a solar or sub-solar metallicity for young and intermediate-age clusters (see, e.g., D'Orazi et al 2011;Spina et al 2017, and references therein). However, it is in agreement with what is expected from standard chemical evolution (e.g., Minchev et al 2013, and references therein) and recent results of a super-solar metallicity ([Fe/H] ≈ +0.2) for some young or intermediate-age clusters in the solar neighborhood, such as NGC 6067 (Alonso-Santiago et al 2017) and Praesepe (D'Orazi et al 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Taking the error weighted average of published cluster parameters (see Table.1) we find an age of 90 ± 20 million years, a distance of 1.88 ± 0.10 kpc, a reddening of E(B-V)= 0.35 ± 0.03, a tidal radius of 12.3 arcminutes and a heliocentric radial velocity of -39.79 ± 0.57 km/s. These are in excellent agreement with findings of the most recent cluster study 17 [20][21][22] for the adopted cluster parameters and accounting for the time since the star left the MS and passed through the AGB phase, predict a PN progenitor mass of 5.58 −0.43 +0.62 ⨀ . Such a high mass for a PN progenitor is unprecedented and provides a key new datum at the poorly studied IFMR high-mass end.…”
supporting
confidence: 89%
“…These two clusters, at a galactocentric distances around 10 kpc, show a metallicity comparable to that of the LMC. Alonso-Santiago et al (2017) suggested that metallicity inhibits the formation of Cepheids. Nevertheless, the absence of Cepheids in low-metallicity environments such as NGC 2345 and NGC 3105 casts doubts on that possibility since both are massive enough clusters to serve as stellar evolution testbeds.…”
Section: Starmentioning
confidence: 99%